Effect of Selected Music Soundtracks on Cardiac Vagal Control and Complexity Assessed by Heart Rate Variability - Parizek, D; Visnovcova, N; Hamza Sladicekova, K; Veternik, M; Jakus, J; Jakusova, J; Visnovcova, Z; Ferencova, N; Tonhajzerova, I (Physiological research, 2023)
UNLABELLED: Listening to music is experimentally associated with positive stress reduction effect on human organisms. However, the opinions of therapists about this complementary non-invasive therapy are still different. PURPOSE: The aim of our study was to investigate the effect of selected passive music therapy frequencies without vocals on selected cardio-vagal and complexity indices of short-term heart rate variability (HRV) in healthy youth, in terms of calming the human. MAIN METHODS: 30 probands (15 male, averaged age: 19.7+/-1.4 years, BMI: 23.3+/-3.8 kg/m2) were examined during protocol (Silence baseline, Music 1 (20-1000 Hz), Silence 1, Music 2 (250-2000 Hz), Silence 2, Music 3 (1000-16000 Hz), and Silence 3). Evaluated HRV parameters in time, spectral, and geometrical domains represent indices of cardio-vagal and emotional regulation. Additionally, HRV complexity was calculated by approximate entropy and sample entropy (SampEn) and subjective characteristics of each phase by Likert scale. RESULTS: the distance between subsequent R-waves in the electrocardiogram (RR intervals [ms]) and SampEn were significantly higher during Music 3 compared to Silence 3 (p=0.015, p=0.021, respectively). Geometrical cardio-vagal index was significantly higher during Music 2 than during Silence 2 (p=0.006). In the subjective perception of the healthy youths evaluated statistically through a Likert scale, the phases of music were perceived significantly more pleasant than the silent phases (p<0.001, p=0.008, p=0.003, respectively). CONCLUSIONS: Our findings revealed a rise of cardio-vagal modulation and higher complexity assessed by short-term HRV indices suggesting positive relaxing effect music especially of higher frequency on human organism.
Keywords: Young Adult; Electrocardiography; Male; nervus vagus; mladý dospělý; Adolescent; srdce; hudba; Heart Rate; Adult; dospělí; mužské pohlaví; srdeční frekvence; mladiství; Music; lidé; Humans; Vagus Nerve; Heart; elektrokardiografie